Investigation of alternative pinless screw concepts for rubber extrusion - Schmidt, Leon; Brüning, Florian (KGK - Kautschuk Gummi Kunststoffe)
Keywords: extrusion; Kautschuk

Consideration of modeled pressure dependent viscosity data in injection molding simulation - Hanselle, Felix Paul; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Keywords: Druckabhängigkeit; Rheologie; Simulation; Spritzgießen; Viskosität

Influence of pre-shearing on the rheological properties of filled rubber compounds - Kleinschmidt, Dennis; Brüning, Florian (KGK Kautschuk Gummi Kunststoffe)
Keywords: Rheologie; Viskosität; Wandgleiten

Beschreibung des Mischverhaltens von Kautschukstiftextrudern mittels simulativer und experimenteller Methoden - Kleinschmidt, Dennis (Extrusion - Grundlagen und Praxis)

Analyse des thermo-chemischen Devulkanisationsverhaltens von SBR-basierten GTR-Mischungen - Petzke, Jonas Dirk Rudolf Helmut (AZuR-Kolloquium 2025)

Improvement of injection molding simulations by application of modeled pressure dependent viscosity data - Hanselle, Felix Paul

NUMERICAL AND EXPERIMENTAL CONSIDERATIONS OF THE CREEP OF THERMOPLASTIC FLANGE SYSTEMS FOR THE DEVELOPMENT OF AN ANALYTICAL CALCULATION METHOD - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (Proceedings of the ASME 2025 Pressure Vessels & Piping Conference PVP2025)

Einfluss von FFF-Prozessparametern auf die elektrische Leitfähigkeit von leitfähigen TPE-Komposite - Salm, Maximilian Karl Franz; Moritzer, Elmar (Technomer 2025 29. Fachtagung)
Keywords: Additive Fertigung; Elektrische Leitfähigkeit; Compounds; TPE; Fused Filament Fabrication

Einfluss der Schichtstruktur auf die Druckfestigkeit von FDM-Bauteilen – Ein konzeptioneller Ansatz - Beutelspacher, Jonas; Scharwald, David; Moritzer, Elmar (Technomer 2025 29. Fachtagung)

Impact of non-rotationally symmetric joint orientation on neighbouring joints and component performance in lap shear specimens - Devulapally, Deekshith Reddy; Steinfelder, Christian; Tröster, Thomas; Brosius, Alexander (MATEC Web of Conferences)
This paper discusses the influence of joint orientation with non-rotationally symmetric geometry, on load distribution and structural behavior. The focus is on understanding how changes in the alignment of individual joints affect the distribution of load, neighboring joints, and the overall performance of the component. Lap shear specimens with multiple joints arranged in a line are analyzed to explore these effects. Simplified models are used to model the joints in finite element simulations, allowing for efficient yet accurate analysis of the load distribution and structural response under varying joint orientations. Variations in joint orientation result in measurable changes in the distribution of forces on adjacent joints, influencing their behavior and that of the overall assembly. Experimental validation confirms the numerical results, providing deeper insights into the interaction between individual joints and their surroundings. This work contributes to the development of systematic approaches for optimizing the design of components with non-rotationally symmetric joints. The study highlights the importance of considering directional properties of joints in designing structural components.

Methodische Auswahl hochfester Mehrphasenstähle bezüglich ihrer lokalen und globalen Duktilität - Tröster, Thomas; Marten, Thorsten; Luig, Simon

Localized Ultrasonic Cleaning for Injection Mold Cavities: A Scalable In Situ Process with Surface Quality Monitoring - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Marten, Thorsten (Technologies)
As global industries seek to reduce energy consumption and lower CO2 emissions, the need for sustainable, efficient maintenance processes in manufacturing has become increasingly important. Traditional mold cleaning methods often require complete tool disassembly, extended downtime, and heavy use of solvents, resulting in high energy costs and environmental impact. This study presents a novel localized ultrasonic cleaning process for injection molding tools that enables targeted, in situ cleaning of mold cavities without removing the tool from the press. A precisely positioned ultrasonic transducer delivers cleaning energy directly to contaminated areas, eliminating the need for complete mold removal. Multiple cleaning agents, including alkaline and organic acid solutions, were evaluated for their effectiveness in combination with ultrasonic excitation. Surface roughness measurements were used to assess cleaning performance over repeated contamination and cleaning cycles. Although initial tests were performed manually in the lab, results indicate that the method can be scaled up and automated effectively. This process offers a promising path toward energy-efficient, low-emission tool maintenance across a wide range of injection molding applications.

Intrinsic production of metal-carbon fiber reinforced plastic hybrid shafts using vacuum-assisted resin transfer molding - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Ellouz, Manel; Kordisch, Thomas (Journal of Composite Materials)
Over the past decades, the importance of lightweight structures in the aircraft and automotive industries has steadily increased due to regulations aimed at reducing global warming. Work hardened steel alloys are commonly used for lightweight applications, but they face stability issues when the material thickness reaches certain thresholds. Fiber Reinforced Plastics (FRP) offer a viable alternative due to their high strength-to-weight ratio, but they are often expensive due to long production cycles and high material costs. A feasible solution lies in hybrid lightweight designs that utilize expensive FRP materials only in highly stressed areas, achieving a balance between low mass and acceptable cost. These hybrid structures are lighter than metal components and more cost-effective compared to fully FRP structures, without compromising mechanical properties. This study focuses on producing rotationally symmetrical hybrid structures using Resin Transfer Molding (RTM) combined with vacuum assistance in a single-stage process. The research examines the effects of injection pressure, mold temperature, and the interface between metal and FRP. The mechanical characterization of these hybrid structures was conducted to assess their performance under torsion, compression, and interlaminar shear strength (ILSS) loading conditions. The results indicate that hybrid designs can offer a lightweight alternative without compromising mechanical properties.

Process Development for Hybrid Brake Pedals Using Compression Molding with Integrated In-Mold Assembly - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Lückenkötter, Julian Janick Stefan; Tröster, Thomas; Marten, Thorsten (Polymers)
Currently, the need for resource efficiency and CO2 reduction is growing in industrial production, particularly in the automotive sector. To address this, the industry is focusing on lightweight components that reduce weight without compromising mechanical properties, which are essential for passenger safety. Hybrid designs offer an effective solution by combining weight reduction with improved mechanical performance and functional integration. This study focuses on a one-step manufacturing process that integrates forming and bonding of hybrid systems using compression molding. This approach reduces production time and costs compared to traditional methods. Conventional Post-Mold Assembly (PMA) processes require two separate steps to combine fiber-reinforced plastic (FRP) structures with metal components. In contrast, the novel In-Mold Assembly (IMA) process developed in this study combines forming and bonding in a single step. In the IMA process, glass-mat-reinforced thermoplastic (GMT) is simultaneously formed and bonded between two metal belts during compression molding. The GMT core provides stiffening and load transmission between the metal belts, which handle tensile and compressive stresses. This method allows to produce hybrid structures with optimized material distribution for load-bearing and functional performance. The process was validated by producing a lightweight hybrid brake pedal. Demonstrating its potential for efficient and sustainable automotive production, the developed hybrid brake pedal achieved a 35% weight reduction compared to the steel reference while maintaining mechanical performance under quasi-static loading

Optimizing Injection Molding Tool Design with Additive Manufacturing: A Focus on Thermal Performance and Process Efficiency - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Marten, Thorsten (Materials)
Injection molding plays a pivotal role in modern manufacturing, enabling the mass production of complex components with high precision. However, traditional tooling methods often face challenges related to thermal management, design constraints, and material efficiency. This study examines the use of additive manufacturing (AM) in the development and optimization of injection molding tools to overcome these limitations. A novel prototype was fabricated using AM techniques, incorporating integrated cooling channels and optimized lattice structures to enhance thermal performance and simplify the manufacturing process. Experimental validation demonstrated the prototype’s effective integration into a vacuum-assisted resin transfer molding (VA-LRTM) system without requiring modifications to existing tooling setups. The results showed significant improvements in temperature regulation, reduced cycle times, and consistent mechanical properties of the molded components compared to conventional approaches. By reducing the number of tool components and eliminating the need for support structures during manufacturing, AM also minimized material waste and post-processing requirements. This research highlights the transformative potential of additive manufacturing in injection molding tool design, offering increased flexibility, cost efficiency, and enhanced functionality to meet the evolving demands of modern industrial applications.

Assessment of the influence of curing parameters on fibre reinforced epoxy composite properties using guided ultrasonic waves - Irmak, Hayrettin; Claes, Leander; Wu, Shuang; Marten, Thorsten; Tröster, Thomas (2025 International Congress on Ultrasonics)
The degree of crosslinking in unidirectional prepreg materials was investigated using differential scanning calorimetry to assess their curing behavior and thermal characteristics. To complement these measurements with a non-destructive, in-situ method, the propagation properties of guided acoustic waves in cured carbon fibre-reinforced epoxy plates were analysed. Correlations between the degree of crosslinking and acoustically determined mechanical properties were drawn to enable a future non-destructive evaluation approach.
Keywords: fibre-reinforced polymers; differential scanning calorimetry; degree of crosslinking; guided waves; ultrasound

Transfer of powder-based direct coating in the injection molding process from two dimensional components to three-dimensional components - Moritzer, Elmar; Lingnau, Kai Martin (The 40th International Conference of Polymer Processing Society)

Werkstofflicher Ansatz zum adhäsiv-basierten Fügen für hochflexible TPE-Organobleche als Verstärkungsstruktur - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Influence of the processing parameters on the mechanical strenght of injection moulded BMC components for direct screwing - Held, Christian; Moritzer, Elmar (the 40th International Conference of Polymer Processing Society)

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)